2018
DOI: 10.7897/2230-8407.097122
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Medicinal Plants With Antidiabetic Activity From Rubiaceae Family

Abstract: Medicinal plants play an important role in the management of diabetes mellitus, especially in developing countries. A comprehensive review is conducted to accumulate information about medicinal plants with hypoglycemic properties. Rubiaceae represents one of five families of the most species-rich flowering plants. The Rubiaceae family is the largest plant family of 617 genera and about 13,137 species found worldwide, especially in the tropics and subtropics. Based on searches in several scientific journals, 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Suku Rubiaceae terdiri atas 10.700 spesies dan merupakan salah satu suku Angiosperm terbesar (Mongrand et al, 2005). Tanaman suku Rubiaceae telah lama digunakan dalam bidang kesehatan dan oleh masyarakat Indonesia untuk pengobatan tradisional (Sadino, 2018;Marusin et al, 2013), dimana beberapa diantaranya mampu menunjukkan efek antibakteri, antivirus, antiinflamasi, antioksidan dan analgesik (Heitzman et al, 2005). Kandungan kafein salah satu spesies tanaman Rubiaceae yaitu Coffea arabica banyak digunakan untuk obat migrain maupun untuk stimulan sistem saraf, diuretik, vasokonstriktor, dan bronchodilator (Simoes et al, 2004).…”
Section: Peran Tanaman Suku Rubiaceae DI Bidang Kesehatanunclassified
“…Suku Rubiaceae terdiri atas 10.700 spesies dan merupakan salah satu suku Angiosperm terbesar (Mongrand et al, 2005). Tanaman suku Rubiaceae telah lama digunakan dalam bidang kesehatan dan oleh masyarakat Indonesia untuk pengobatan tradisional (Sadino, 2018;Marusin et al, 2013), dimana beberapa diantaranya mampu menunjukkan efek antibakteri, antivirus, antiinflamasi, antioksidan dan analgesik (Heitzman et al, 2005). Kandungan kafein salah satu spesies tanaman Rubiaceae yaitu Coffea arabica banyak digunakan untuk obat migrain maupun untuk stimulan sistem saraf, diuretik, vasokonstriktor, dan bronchodilator (Simoes et al, 2004).…”
Section: Peran Tanaman Suku Rubiaceae DI Bidang Kesehatanunclassified
“…A review article on Mitracarpus spp (38) reported studies on phytochemical screening of the leaf extract of Mitracarpus vilosus which revealed potent saponin, steroids, and cardiac glycoside constituents (39,40). Ibrahim et al who explored the antibacterial efficacy of Mitracarpus vilosus extract on some selected multidrug resistance clinical isolates also reported the presence of saponin, tannins alkaloids, terpenoids, steroids, anthraquinones, flavonoids, and phenols in the acetone extract (41). Moreso, studies have shown that the presence of alkaloids, saponins, cardiac glycosides, and tannins were present in the ethanol leaf extract of M. scaber zucc which is another family of Mitracarpus sp.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…The secondary metabolites of the Rubiaceae family have a high medicinal potential, and this factor can be used as a marker for genera and subfamilies in chemical taxonomy [3]. Different species of this family have been investigated in terms of the potential for biological activities, such as antiplasmodial [4], antibacterial [5,6], antiinflammatory [7], and anti-diabetic activities [8]. The genus Crucianella is a flowering plant that belongs to the Rubiaceae family.…”
Section: Introductionmentioning
confidence: 99%